2017
DOI: 10.1111/hsc.12504
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effectiveness of interpreted consultations: Australian interpreter, general practitioner and patient perspectives

Abstract: Healthcare consultations with patients lacking English proficiency are challenging for all parties, even in Australian primary care where the engagement of interpreters is encouraged and fully subsidised. Our objective was to understand these challenges from the perspectives of interpreters, patients and general practitioners in order to improve the effectiveness of interpreted consultations. Our investigator team approached the interpreted consultation as an interprofessional collaboration. A convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
5
11
0
1
Order By: Relevance
“…These time constraints compromise quality in the sense that interpreters are not always able to provide verification of patient understanding. This finding is in consonance with Sturman et al (2018) who found that the placing of time constraints on interpreters was a systemic practice that resulted in interpreters, general practitioners, and patients all "feeling rushed in some consultations, which tended to reduce their effectiveness, particularly if the doctor appeared impatient to the others present" (p. 235). Thus, there is general agreement that more time needs to be allocated for interpreter-mediated consultations for them to be effective.…”
Section: Institutional Barrierssupporting
confidence: 80%
“…These time constraints compromise quality in the sense that interpreters are not always able to provide verification of patient understanding. This finding is in consonance with Sturman et al (2018) who found that the placing of time constraints on interpreters was a systemic practice that resulted in interpreters, general practitioners, and patients all "feeling rushed in some consultations, which tended to reduce their effectiveness, particularly if the doctor appeared impatient to the others present" (p. 235). Thus, there is general agreement that more time needs to be allocated for interpreter-mediated consultations for them to be effective.…”
Section: Institutional Barrierssupporting
confidence: 80%
“…cutting the interpreter short in order to introduce a new topic) and at times even responded to the EOs before these were translated. Doctors' own time constraints and at times their inability to allow for interpretation [40,41] resulted in EOs being left untranslated. This finding confirms that many doctors have not received any training on how to hold IMCs [42].…”
Section: Discussionmentioning
confidence: 99%
“…Das beschriebene tiefe Vertrauen der Schwangeren und jungen Mütter in die Arbeit der Sprach-und Integrationsmittlerinnen und die dargestellten positiven Effekte der Begleitungen auf die geburtshilfliche Versorgung unterstreichen die bekannten wissenschaftlichen Erkenntnisse zum Nutzen der Hinzuziehung von Sprach-und Integrationsmittlerinnen (Borde, 2018;Brenne et al, 2013;Divi et al, 2007;RundUm. Ergebnisbroschüre, 2020) Interprofessionelle Trainings mit den professionellen Akteuren/innen des Gesundheits-und Sozialwesens dienen dazu, voneinander zu lernen und sind wertvoll für die Schaffung von gegenseitigem Verständnis und Respekt (Gün, 2018;Sturman et al, 2018). Relevante Ergebnisse, die durch zeitlich begrenzt geförderte Projekte wie RundUm generiert wurden, müssen als wissenschaftliche Fundierung Einfluss auf Anschlussfinanzierungen finden.…”
Section: Bedeutung Der Individuellen Ausgestaltung Der Tätigkeit Als Sprach-und Integrationsmittlerinunclassified